Legacy Lead in Urban Garden Soils: Communicating Risk and Limiting Exposure - Paltseva, Anna A.; Cheng, Zhongqi; McBride, Murray; Deeb, Maha; Egendorf, Sara Perl; Groffman, Peter M. (Frontiers in Ecology and Evolution, 2022)
Lead exposure has long been recognized as a hazard to human health. Urban garden soils often contain elevated levels of Pb, mainly from legacy sources, and is a main barrier for urban gardening. The actual risk from soil Pb is rather complicated and can vary significantly in real urban and suburban settings. The capacity of gardeners to access, understand, and act on scientific data related to soil contamination is also variable. These had led to crippling confusion and uncertainty among urban gardening stakeholders, with inconsistent recommendations and policies. This is a great failure at the interface between science and society. This review paper briefly summarizes the current scientific knowledge on soil Pb in urban gardens. Our objective is to produce clear recommendations about assessing actual risk and limiting exposure. These recommendations include: (1) urban soil testing should be prioritized because of the high probability of Pb contamination, and that urban gardening should not begin until thorough testing or prophylactic remediation has been done; (2) documentation of land-use history information should be required in all property transactions so that the potential for soil (and other) contamination can be clearly identified; (3) amendments cannot be relied upon as a treatment for contaminated soils to reduce risk to gardeners because it does not always work; (4) certain crops are much less susceptible to contamination than others and thus should be prioritized in urban gardens; (5) wherever feasible, raised beds filled with upcycled local mineral and organic materials are the preferred substrate for urban gardening.